Taste dysfunction as a predictor of depression in schizophrenia: A systematic review and meta-analysis. - Jia Liu; Shu-Jie Sun; Ye Lu; Xin Ping; Wan Zhang; Lin Pei (PLoS ONE)
Objective This study aims to investigate the relationship between taste dysfunction and depression among patients with schizophrenia, to achieve early detection of depression in clinical practice. Methods Following PRISMA guidance, a comprehensive literature search was conducted globally, covering papers published from 1961 to June 2023. A total of 17 manuscripts were selected through meta-analysis and sensitivity analysis after examining available materials from seven databases to determine the correlation between depression and taste dysfunction. Results The comparison of the 17 selected manuscripts revealed that individuals with gustatory dysfunction may be more likely to experience depressive symptoms (SMD, 0.51, 95% CI, 0.08 to 0.93, p = 0.02). Depression is associated with taste dysfunction in certain aspects, as indicated by the pleasantness ratings of sucrose solutions (SMD, -0.53, 95% confidence interval [CI] -1.11 to 0.05, p = 0.08), gustatory identification ability (SMD, 0.96, 95% CI, 0.03 to 1.89, p = 0.04), and the perception threshold of sweet taste (MD, 0.80, 95% CI, 0.79 to 0.81, p < 0.00001). Conclusions Due to variations in the methods, designs, and selection criteria employed in the included studies, it is necessary to establish a feasible framework. Future research using detailed and targeted approaches can provide clearer and more unified conclusions on the relationship between taste dysfunction and depression. Moreover, further high-quality research is needed to obtain clearer conclusions and explore the potential of taste dysfunction as an effective tool for early screening of depression. Trial registration This review has been registered in the PROSPERO on April 2022 with the identifier CRD42023400172.